Correlation Between Vocabulary Achievement of Computer Engineering Network (TKJ) Students and Their Learning Habit Using Computer at SMKN 1 Pulubala - Septiansi Akuba; Sartin T. Miolo; Rahmawaty Mamu (Jambura Journal of English Teaching and Literature, 2022)
The objective of this research is to obtain the empirical data about the correlation between vocabulary achievement of Computer Engineering Network (TKJ) students and their learning habit using computer at SMKN 1 Pulubala. This research use correlation method and quantitative descriptive design to measure the correlation. This research was conducted to 67 Computer Engineering Network (TKJ) students at SMKN 1 Pulubala. After doing the research, the researcher concluded that there is a correlation between vocabulary achievement of Computer Engineering Network (TKJ) students and their learning habit using computer. It can be seen through the result of the correlation calculate using SPSS Computer for Windows show a value of 0.507. Based on the interpretation of the correlation result, it can be concluded that correlation between vocabulary achievement of Computer Engineering Network (TKJ) students and their learning habit using computer has medium correlation. The researcher has also measured the influence of correlation between vocabulary achievement of Computer Engineering Network (TKJ) students and their learning habit using computer found 91.04% in the frequency of learning habit and 80.59% in verb. Keyword: vocabulary, learning habit, correlation